2003
DOI: 10.1007/s00455-002-0086-z
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Variability During Hypopharyngeal Bolus Transit

Abstract: The pharyngeal phase of deglutition is considered to occur in a reflexive, preprogrammed fashion. Previous studies have determined a general sequence of events based on the mean timing of bolus transit and swallowing gestures. Individual variability has not been studied, however. The purpose of this study was to determine the amount of sequence variability that normally occurs during the hypopharyngeal phase of deglutition. Dynamic swallow studies from 60 normal volunteers were evaluated and event sequence var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
56
3
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(73 citation statements)
references
References 12 publications
12
56
3
2
Order By: Relevance
“…In a contrasting approach, Kendall and colleagues [13] sequenced both gestural and bolus events from the lateral view videofluoroscopies of 60 healthy volunteers (30 male) between 18 and 62 years of age, who each swallowed one bolus each of 1, 3, and 20ml Liquid Barosperse Barium Sulfate Suspension (60% w/v). The analysis investigated the degree to which the sequence varied for 12 separate event pairs, drawn :from the following events of interest:…”
Section: Introductionmentioning
confidence: 99%
“…In a contrasting approach, Kendall and colleagues [13] sequenced both gestural and bolus events from the lateral view videofluoroscopies of 60 healthy volunteers (30 male) between 18 and 62 years of age, who each swallowed one bolus each of 1, 3, and 20ml Liquid Barosperse Barium Sulfate Suspension (60% w/v). The analysis investigated the degree to which the sequence varied for 12 separate event pairs, drawn :from the following events of interest:…”
Section: Introductionmentioning
confidence: 99%
“…any research studies have explored the sequence of the events of swallowing and have revealed that there is considerable variability between and within healthy individuals (Cook et al, 1989;Gay, Rendell, Spiro, Mosier, & Lurie, 1994;Kendall, 2002;Kendall, Leonard, & McKenzie, 2003;Kendall, McKenzie, Leonard, Gonçalves, & Walker, 2000;Logemann et al, 2000;Logemann, Pauloski, Rademaker, & Kahrilas, 2002;McConnel, Cerenko, Jackson, & Guffin, Jr., 1988;Mendell & Logemann, 2007;Ohmae, Logemann, Kaiser, Hanson, & Kahrilas, 1995). Factors contributing to this variability include bolus volume, bolus consistency, age, and gender (Cook et al, 1989;Kendall, 2002;Kendall et al, 2003;Logemann et al, 2000Logemann et al, , 2002Mendell & Logemann, 2007;Ohmae et al, 1995).…”
mentioning
confidence: 99%
“…Factors contributing to this variability include bolus volume, bolus consistency, age, and gender (Cook et al, 1989;Kendall, 2002;Kendall et al, 2003;Logemann et al, 2000Logemann et al, , 2002Mendell & Logemann, 2007;Ohmae et al, 1995). In individuals with dysphagia, the sequence of swallowing events is different from normal swallowing, likely due to the underlying swallowing disorder (Bisch, Logemann, Rademaker, Kahrilas, & Lazarus, 1994;Ekberg, 1986).…”
mentioning
confidence: 99%
“…3) Após a passagem do bolo alimentar pela transição faringo-esofágica, resultante da entrada de resíduos alimentares na região faríngea (32) .…”
Section: 3unclassified
“…O mecanismo básico de proteção laríngea consiste na inibição reflexa da respiração, fechamento do esfíncter glótico, elevação e deslocamento anterior da laringe em aproximação com o osso hióide, ficando sob a proteção da língua (30,31,32) .…”
Section: R Re Ev VI Is Sã ãO O D Da a L Li It Te Er Ra At Tu Ur Ra A 18unclassified